Anarcha-Feminism and Sustainable Development Goals: Case of Kurdish Women Protection Unit (YPJ) - M. Hafizh Nabiyyin (Epistemik: Indonesian Journal of Social and Political Science, 2023)
The emergence of the pseudo-state Autonomous Administration of North and East Syria (AANES) or better known as Rojava in 2014 became an alarm for the emergence of a new form of political entity that transcends the form of the Westphalian nation- state. The democratic confederalism system is seen as very close to the thought of anarchism which rejects all forms of hierarchy including the nation-state system and upholds equality between human beings. YPJ is a women's armed forces unit in Rojava that adheres to the idea of Jineology –an idea of gender equality from Abdullah Ocalan which is also integrated into the democratic confederacies system. The magnitude of the role of YPJ in the process of Rojava's resistance to the nation-state and capitalism made the writer interested in analyzing YPJ resistance using the Anarcha-Feminism theory to determine the effect of the theory on YPJ resistance. Anarcha-Feminism was chosen because it can be a synthesis between class struggle, women's liberation, and the deconstruction of the nation-state political system. This research will also review and describe the role of women in post-conflict development in Rojava, particularly regarding their involvement in the economy, education, social, military, and public decision-making through the perspective of the Sustainable Development Goals.